Spontaneous activity rates and resting metabolism: Support for the allocation model of energy management at the among‐individual level. (1st October 2019) - Biro, Peter A.; Thomas, Frédéric; Ujvari, Beata; Adriaenssens, Bart; Beckmann, Christa
Abstract: Despite continuing interest in the proximate energetic constraints on individual variation in behavior, there is presently equivocal evidence for correlations between metabolism and behavior at the among‐individual level. Possible reasons for this include imprecise estimates of individual mean behavior and metabolism due to no repeated measures on one or more of the traits, analyses that do not take into account the labile nature of these traits and the uncertainty in individual estimates, and changing environmental conditions not accounted for. In this empirical study, we repeatedly measured activity rates and resting metabolic rates (RMR) of individual male mosquitofish over an extended period, lasting several months under constant laboratory conditions. Repeatability of each trait was significant (RMR: R = .41; activity: R = .72), indicating consistent variation among individuals, making covariance between them possible. Contrary to expectations, bivariate mixed model analysis revealed that more active individuals had lower RMR ( r = −.58) after accounting for mass effects and other covariates. This result suggests that high activity rates require individuals to allocate less energy toward maintenance, and thus provides evidence for the "allocation" model of energy management. We suggest that it would be valuable to study whether and how behavior‐RMR correlations change over individual lifetime, a topic that has yet to be addressed.